1961
DOI: 10.1021/ed038p357
|View full text |Cite
|
Sign up to set email alerts
|

Surface area of activated charcoal by Langmuir adsorption isotherm

Abstract: The purpose of this paper is to suggest an interpretation of the experimental data to make the determination of the surface area of activated charcoal by Langmuir adsorption isotherm more meaningful for the student.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…( 3 ) where the constants q m and K , are related to the adsorption capacity and the energy of adsorption, respectively. The graph of C e / Q e vs C e was plotted to determine the Langmuir isotherm constants [ 42 , 43 ]. …”
Section: Methodsmentioning
confidence: 99%
“…( 3 ) where the constants q m and K , are related to the adsorption capacity and the energy of adsorption, respectively. The graph of C e / Q e vs C e was plotted to determine the Langmuir isotherm constants [ 42 , 43 ]. …”
Section: Methodsmentioning
confidence: 99%
“…The adsorption Langmuir equilibrium constants and estimated surface area based on AA and MB onto Jatropha fruit pericarp sodium chloride activated carbon (JPS) are presented in Table 3. The specific surface area of monolayer coverage was determined from the value of X m based on the published reports [20,21]. From Table 3 The observed surface area based on MB adsorption is within the range of 600-1000 m 2 /g obtained from activated carbons from similar and related raw materials based on MB adsorption [3,7].…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…In addition, the Langmuir constant Q o obtained from the Langmuir isotherm represents the practical limiting adsorption capacity and is useful in comparing the performance of different adsorbents. It correlates well with specific surface area, and it relates directly with the amount of adsorbate bound from the solution. In the present study, higher adsorption capacity for MIP was observed likely due to large complementary cavities of the template and larger surface area created by the imprinting process.…”
Section: Discussionmentioning
confidence: 99%